Functional miRNA-based Phenotypic Screening as a tool to delineate HIV-host interactions and facilitate Novel Drug Discovery - Naidoo, Jerolen (Division of Immunology, 2021)
Human Immunodeficiency Virus (HIV) is the causative agent of AIDS, a disease which affects over 24 million people globally and for which there is neither curative treatment nor vaccine available. As an intracellular pathogen that encodes only 15 proteins HIV-1 is highly dependent upon its host's cellular machinery in order to complete its life cycle. Host-directed therapy thus represents a potentially lucrative strategy for the development of novel anti-HIV therapies. microRNAs (miRNAs) are short noncoding RNA molecules that function as part of the endogenous RNA interference system which governs post transcriptional gene regulation. Current knowledge has placed miRNAs at the crux of HIV-host interactions, yet the functional relevance of the majority of the human miRNAome with regards to HIV replication has remained unknown. A microscopy-based high content screening (HCS) approach was thus developed to systematically evaluate the significance of augmenting or inhibiting the function of individual host miRNAs on the replication dynamics of HIV. A bespoke image analysis and data mining pipeline recovered 56 host miRNAs associated with suppressed HIV replication and 28 host miRNAs associated with enhanced HIV replication. Notably, the HIV-modulating potential of 80 of these miRNAs was previously unknown. Furthermore, HCS also uncovered a novel role for the miR-200 family in the modulation of HIV replication. In silico miRNA target identification and pathway enrichment analysis identified 24 pathways associated exclusively with suppressed HIV replication, 10 pathways associated exclusively with enhanced HIV replication and 38 functional pathways enriched for both enhanced and suppressed viral replication. These included a number of pathways previously implicated in HIV replication such as the PI3K, MAPK, TNF and WNT signalling pathways but also revealed novel functional associations including that of the Hippo signalling pathway. Intriguingly pathway analysis revealed an enrichment for host factors associated with viral carcinogenesis and a convergence on host processes and functional targets classically associated with chemotherapy including host DNA damage repair, cell cycle and tyrosine kinase receptor-mediated signalling. Experimental validation confirmed that HIV replication induced an aberrant cell survival phenotype in response to chemically induced DNA damage but this effect was reversed when DNA damage was induced prior to HIV exposure. A series of compound-based validation screens were thus undertaken in order to verify the functional associations recovered by miRNA screening. A targeted collection of 293 small molecule inhibitors, including a number of FDA-approved chemotherapeutics, were screened for HIV modulating activity. Novel anti-HIV activity was recovered for over 40 compounds including a number of FDA-approved therapies. Compound-target enrichment analysis revealed a strong concordance with functional associations initially described by miRNA-based HCS including EGFR-mediated signalling and DNA damage repair. Concordant HIV-suppressive activity was also recovered for miRNAs and compounds with common functional targets. The outcomes of this study thus represent a significant and novel contribution to current knowledge on HIV-host interactions. Furthermore, these findings have characterised novel miRNA and small molecule candidates for the treatment of HIV and have successfully demonstrated the utility of miRNA-based HCS for novel-drug discovery and drug repositioning.